Measuring parents' regulatory media use for themselves and their children - Suh, Bolim; Kirkorian, Heather; Barr, Rachel; Kucker, Sarah C.; Torres, Chioma; Radesky, Jenny S. (Frontiers in Developmental Psychology, 2024)
Parents often use media to manage their own or their child's emotions and behaviors, which is called "regulatory media use". While the use of media to alleviate negative emotions and behaviors may be helpful in the short-term, there may be negative consequences in the long-term (e.g., for children's development of self-regulatory skills). Research remains limited, often relying on a single, binary question asking whether a parent ever uses media to calm their child.To enable future research on the effects of regulatory media use, this paper described initial scale development efforts for measuring parents' regulatory media use for themselves (parent scale) and their children (child scale). These scales were tested in an aggregate sample of parents with children 1-10 years old, and with each of three subsamples representing parents of children in infancy (15-25 months old), early childhood (2-5 years old), and middle childhood (5-10 years old). Overall, the results provide initial support for the scales as a reliable tool for measuring regulatory media use. Both scales for parents and children had a stable three-factor structure that held within each of the three subsamples. Further, both scales had predictive validity, each predicting parenting stress and child screen time. Potential uses of the measure and implications for future studies are discussed.